B Lymphocytes Are a Predictive Marker of Eribulin Response and Overall Survival in Locally Advanced or Metastatic Breast Cancer: A Multicenter, Two-Cohort, Non-Randomized, Open-Label, Retrospective Study - Tashireva, Liubov A.; Popova, Nataliya O.; Kalinchuk, Anna Yu.; Goldberg, Viktor E.; Kovalenko, Elena I.; Artamonova, Elena V.; Manikhas, Aleksey G.; Ponomarenko, Dmitriy M.; Levchenko, Nataliya V.; Rossokha, Elena I.; Krasilnikova, Svetlana Yu.; Zafirova, Marina A.; et al. (Frontiers in Oncology, 2022)
Triple-negative breast cancer has no specific treatment and unfavorable prognosis. Eribulin is one of the drugs widely used in this cohort of patients. In addition to its antimitotic effect, eribulin has an immunomodulant effect on the tumor microenvironment. In this study, we discover immunological markers, such as tumor-infiltrating lymphocytes, CD8+, CD4+, FoxP3+, CD20+ lymphocytes, and their PD1 positivity or negativity, with the ability to predict benefits from eribulin within locally advanced or metastatic triple-negative breast cancer. The primary objective was to explore the association of composition of immune cells in the microenvironment with response to eribulin. The key secondary objective was overall survival. Seven-color multiplex immunofluorescence was used to phenotype lymphocytes in the primary tumor. It has been shown that the PD1-negative-to-PD1-positive B cells ratio in primary tumors more than 3 is an independent predictor of the short-term effectiveness of eribulin [OR (95%CI) 14.09 (1.29-153.35), p=0.0029] and worse overall survival [HR (95%CI) 11.25 (1.37-70.25), p=0.0009] in patients with locally advanced or metastatic triple-negative breast cancer.